Analisis Framing Berita Kenaikan Tarif Masuk Pulau Komodo dan Pulau Padar di Media Online Kompas.com dan Detik.com - Samuel Yudha Pangestu; Hamid Arifin (Universitas Sebelas Maret (UNS), 2024)
The polemic on the increase in the price of entry fees to the Komodo Island and Padar Islands areas has become an interesting topic of discussion in various online media from July to December 2022. Two online media that are quite active in reporting news related to this polemic are Kompas.com and Detik.com. The many conflicts of interest and parties involved in this polemic provide many perspectives for the media to frame according to their values and ideology. Through this research, researchers want to see how Kompas.com and Detik.com framing news regarding the polemic on the increase in entry fees to the Komodo Island and Padar Island areas. This study will use the framing analysis model proposed by Robert N. Entman, where in this technique framing is divided into 4 main elements, namely define problems, diagnose causes, make moral judgments, treatment recommendations. Through the analysis of Robert N. Entman's framing model, it can be seen what things are highlighted by the media, besides that readers can more easily understand media framing. In this study, it was concluded that Kompas.com and Detik.com have several different points of view to assess and present the parties involved in the polemic on the increase in entry rates to the Komodo Island and Padar Island areas.